Todo iluminado - Liev Schreiber
Elijah Wood (Jonathan Safran Foer), Eugene Hutz (Alex), Boris Leskin (Abuelo), Laryssa Lauret (Lista), Jonathan Safran Foer (Leaf Blower), Jana Hrabetova (Abuela de Jonathan), Stepan Samudovsky (Abuelo de Jonathan), Oleksandr Choroshko (Alexander), Gil Kazimirov (Igor), Zuzana Hodkova (Madre de Alex).
Area-Pirata
Keywords: Genero-Drama